Tinjauan Yuridis Pertahanan Negara Yang Dilakukan Tentara Nasional Indonesia - Sulistyo, Heru Drajat (Universitas Merdeka Madiun, 2020)
Abstractâ€” In The division of tasks and authority in carrying out national defense and security between the Indonesian National Army (TNI) and the Indonesian National Police (POLRI) has been regulated in the 1945 Constitution. The problems in this study are: how is the national defense carried out by the Indonesian National Army in the Indonesian State Administration System and how is the relationship between the Indonesian National Army and the Indonesian National Police implementing the National Defense in the Indonesian State Administration System. The research method used is a normative legal research method and uses secondary data types. The results of the research study, namely: 1) the main task of the Indonesian National Army is to uphold state sovereignty, maintain the territorial integrity of the Unitary State of the Republic of Indonesia based on the Pancasila and the 1945 Constitution of the Republic of Indonesia, and protect the entire nation and the whole of Indonesia's blood spilled from threats and disturbance to the integrity of the nation and state (Article 7 paragraph (1) of Law No. 34 of 2004 concerning the Indonesian National Army) 2) Operational duties other than war carried out by the Indonesian National Army to assist the Indonesian National Police in the framework of security and public order. 3) The defense sector which is the duty of the Indonesian National Army and the security sector which is the duty of the Indonesian National Police cannot be separated.Â Keywordsâ€”: Indonesian National Army; Indonesian National Police; National Defense.